Implementation fidelity of community drug distributors during preventive chemotherapy (PCT) of neglected tropical disesase program in Pwani Region, Tanzania. - Mahende, Muhidin Kassim (My University, 2020)
Background: Neglected Tropical Diseases (NTDs) are available in more than 140 countries globally impacting lives, economies, resources, political and daily life interactions. The World Health Organization (WHO) in conjunction with Ministries of Health is promoting the implementation of the mass drug administration program in endemic countries as a ready tool for the prevention, control and towards the elimination of a group of neglected tropical diseases. These target diseases in the Mass Drug Administration (MDA) programs are lymphatic filariasis (elephantiasis), Oncocerciasis (river blindness), schistosomiasis (snail fever), three soil-transmitted helminthiases (caused by Ascaris, Trichuris, and hookworm), and Trachoma. The study aimed to assess the implementation fidelity of the PCT program in Tanzania from the providers’ perspectives, and together with this, the enabling and inhibiting factors of the program were evaluated. Methods: This was a cross-sectional quantitative study that was conducted to evaluate implementation fidelity of the PCT program and fidelity determinants among community drug distributors in Pwani region. This study utilized a researcher administered questionnaire with the district’s preventive chemotherapy team which is responsible for the delivery of the program. The team includes healthcare providers in primary healthcare facilities, teachers from selected government primary schools and volunteering community members within the selected region. The study was conducted between January and June 2019. The study employed a one-stage cluster sampling method. Participants were then selected from two clusters of the chosen districts namely Rufiji and Kibaha within the Pwani region. This study composed of two clusters each comprising of 80 participants making a total sample size to be 160. Multivariable linear regression analysis was performed to assess the relationship between the hypothesized predictors and the implementation fidelity score. Findings: One hundred and sixty Community drug distributors were recruited in this study of which 75 (46.9%) were males and 85 (53.1%) were females. The mean implementation fidelity score among CDDs was 63.3 (SD 5.8) with a minimum value of 44 and a maximum score of 76. A multivariable linear regression model was performed in two stages, a model with social-demographic features and predictors singly and later on with all determinants in one model. The final model showed the following predictors; Interventional complexity/Easiness of an intervention (Coeff 0.11, p=0.015 95% CI 0.025-0.20), facilitation strategies (Coeff 0.12, p=0.029 95% CI 0.013-0.23), quality of delivery (Coeff 0.15, p=0.01 95% CI 0.025-0.20) and knowledge (Coeff 0.16, p=0.008 95% CI 0.045-0.28) being significant predictors of Implementation fidelity of PCT program in Pwani region. Implementation fidelity among CDDs in Pwani region falls under moderate level classification and 4 predictors emerged as significant factors in determining the level of fidelity. These were facilitation strategies, knowledge of an intervention, interventional complexity/Easiness of intervention and quality of delivery. Conclusion: The community drug distributors in Pwani demonstrated moderate implementation fidelity on the PCT program delivery. The community drug distributors provided an evaluation of how the PCT program is delivered using their perspectives and perceptions to the program itself. We recommend the use of Implementation Science practices as an additional tool in exploring best practices in healthcare. Implementation Science brings together experiences from scientists and evidence makers with the providers of intervention at ground level. This may offer an easy way for transfer of evidence based intervention to other contexts while having a guide which ensures that implementation outcomes are not varying greatly between the where the intervention originates and where it is adopted.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Epidemiology in Implementation Science to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2020